A New Method for Angular Speed Measurement with Absolute Encoder - Akkaya, Ramazan; Kazan, Fatih Alpaslan (Elektronika ir Elektrotechnika, 2020)
The encoders are electromechanical devices that give information about the angular position and the number of turns of the shaft, which they are connected. These devices are divided into digital or analogue according to output types. On digital outputs, the output can be binary coded, gray coded or pulsed. The frequency (M) or period (T) method produces accurate results in pulse-output encoders. However, these methods alone cannot give accurate results in some encoder types, which are saw tooth type encoders that produce analogue outputs in different shapes. In this study, a new method was proposed, which reduces the relative error ratio too much below 1 % in an absolute encoder that produces an analogue output ranging from 0 V to 5 V according to the angular position of the shaft. Unlike in the studies in the literature, M method and Analog Digital Converter (ADC) were used together. Thanks to this proposed method (M + ADC), it is possible to increase the measurement accuracy of the encoders with analogue output in all speed regions.